Analisis Hukum terhadap Kebijakan Bea Masuk Anti Dumping Uni Eropa terhadap Baja Nirkarat Indonesia - Kurnia, Kana; Asyharuddin, M (Komisi Pengawas Persaingan Usaha, 2025)
Indonesia filed a lawsuit with the European Union at the World Trade Organization due to the EU imposing anti-dumping import duties on stainless steel products from Indonesia. The EU argued that the anti-dumping import duties were imposed because the EU suspected that Indonesian steel exporting companies received preferential financing from Chinese banks. This research is intended to examine the form of dumping regulation and the imposition of anti-dumping import duties according to the 1994 General Agreement on Tariffs and Trade and the anti-dumping import duty policy implemented by the European Union on stainless steel from Indonesia. The research method used is normative juridical. Based on this research, it is known that dumping as competition in the form of price in the form of price discrimination or selling below normal prices is something that often occurs in international trade, the European Union's action in imposing anti-dumping import duties on stainless cold rolled steel products from Indonesia is certainly contrary to anti-dumping agreement, where one of the conditions is that there is a loss due to the presence of dumped goods, but in this study there was no such loss because Indonesia's steel market share in the European Union is still low and the imposition of anti-dumping import duties is inappropriate due to the assessment of imports Indonesian steel market share combined with the market share value of steel imports from India.